Characterization of a β-N-acetylglucosaminidase gene and its involvement in the development of Lasioderma serricorne (Fabricius). (June 2018) - Chen, Xiaoyulong; Xu, Kangkang; Yan, Xin; Chen, Chunxu; Cao, Yu; Wang, Yawei; Li, Can; Yang, Wenjia
Abstract: β- N -acetylglucosaminidases (NAGs) are essential enzymes in the chitin degradation process and play important roles in insect molting and metamorphosis. In this study, we identified and characterized a full-length cDNA of NAG1 ( LsNAG1 ) in the cigarette beetle, Lasioderma serricorne (Fabricius). The open reading frame of LsNAG1 was 1821 bp and encoded 606 amino acid residues that contained typical domain structure of NAGs. Phylogenetic analyses suggested that the deduced protein LsNAG1 was orthologous to another insect group I NAGs. Quantitative real-time PCR confirmed that LsNAG1 expression levels peaked periodically in the late larval and late pupal stages. A significantly increased level of LsNAG1 transcripts was observed in larvae exposed to the steroid hormone 20-hydroxyecdysone (20E), indicating LsNAG1 was responsive to 20E. Injection of double-stranded RNA (dsRNA) of LsNAG1 into 4th instar larvae and late pupae significantly reduced LsNAG1 transcript levels in both stages, and led to severe molting defects and high mortality. Compared with the control insects injected with ds GFP, 48% and 83% of the larvae and pupae injected with ds LsNAG1, respectively, died during or soon after molting to the next stage. These results demonstrate that LsNAG1 may play a crucial role in successful larval–pupal and pupal–adult transitions, and could be used as an efficient novel target for storage pest control. Highlights: A β - N -acetylglucosaminidase gene LsNAG1 was identified in Lasioderma serricorne. LsNAG1 expression peaked during molting and pupation. LsNAG1 was significantly up-regulated by 20E injection in vivo. After RNAi of LsNAG1, the beetles failed to molt normally and eventually died.